Detection of Mask Usage Using Image Processing and Convolutional Neural Network (CNN) Methods - Ervan Asri; Yance Sonatha; Indri Rahmayuni; Meri Azmi (Universitas Negeri Padang, 2022)
Since the first case of COVID-19 was discovered in Indonesia in March 2020, the number of positively contaminated patients is increasing every day. On April 13, 2021, there were 1,571,824 patients who were positively contaminated with COVID-19. Various efforts have been made to suppress the spread of this dangerous virus, one of which is by implementing health protocols that must be obeyed when someone is in a crowd. The recommendation to use masks is a form of health protocol. Often people ignore the importance of using masks in public places, sometimes masks are used not in accordance with justified recommendations. For this reason, research is proposed which will later produce a system that can detect whether someone has used a mask correctly. The system was developed using a deep learning method using a convolutional neural network (CNN). CNN will classify data objects in the form of images / user images and determine whether they are wearing masks correctly or not. The output of the system in the form of audio will be delivered through speakers installed adjacent to the camera which will scan the user's face.